ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI PADA KOPI KETJE PANJANG - Dinda Mareta; Herry Goenawan Soedarsa (Jurnal Widya, 2024)
This research aims to determine and analyze the factors that influence consumer interest in Ketje Panjang Coffee. Population is the sum of all possible values, calculated and measured, so that the population of this study are consumers of Ketje Panjang Coffee. The sample in this study was identified using the lemshow formula, it was found that the sample size was 100 respondents. This analysis uses statistical calculations to facilitate testing for data analysis, therefore the above analysis uses the SPSS 25 application tool. This research uses multiple linear regression analysis or tests, coefficient of determination tests and t tests. The research results show that the factors that influence consumer interest, such as consumer satisfaction, product quality, price and promotion, show that they partially influence consumer interest, and product quality is the factor that most influences consumer interest. Ketje Panjang Coffee should improve consumer interest by maintaining consumer satisfaction, product quality, price and promotion with efforts to correct errors in Ketje Panjang Coffee so that consumer interest can increase.